MAPS OF ROMAN DACIA. IV. GRIGORE TOCILESCU AND “LA DACIE ROMAINE” IN 1900 - Florin FODOREAN (Journal of Ancient History and Archaeology)
We are continuing our series of studies regarding the maps of Roman Dacia with this short note regarding the representation of Dacia on a map published by Grigore Tocilescu in his book Fouilles et recherches archéologiques en Roumanie: communications faites à l'Académie des Inscriptions et Belles-Lettres de Paris, 1892-1899, Bucarest, 1900. The map illustrates the level of knowledge concerning the main elements of the topography of Dacia, including the roads and the forts